Determinants of the family physical fitness youth with selected disabilities - Karasiński, Michał (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
The subject of this thesis was the physical fitness of youth with mild intellectual disability, and youth with hearing impairment. The aim of the research was to determine the family factors that affect the results of physical fitness. In the research work, particular attention was paid to: family factors, family structure, educational methods, application of rewards and punishments, parenting style, and socioeconomic status of the family. The practical purpose of this research was to develop practical guidelines for parents to stimulate their children to a higher level of physical fitness development.